Adaptive PID Auto-Tuning Algorithm on Omron PLC for Speed Control and Stability - Liu Kin Men; Akik Hidayat; Nanang Rohadi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2025)
Speed regulation of three-phase induction motors under varying load conditions presents a major challenge in industrial automation due to their nonlinear dynamic behavior. This paper proposes an adaptive speed control system using a proportional-integral-derivative auto-tuning (PIDAT) algorithm implemented on the Omron CP1H-XA40DT-D programmable logic controller (PLC). The initial PID parameters were derived using the Ziegler–Nichols method, and the system continuously monitored the steady-state error during operation. When the error exceeded a predefined 5% threshold, the auto-tuning sequence was triggered. This sequence included a relay feedback test (RFT), system identification using a first order plus dead time (FOPDT) model, and real-time PID parameter recalculation. The system hardware integrated an Omron 3G3MX2 inverter, rotary encoder, and NB7W-TW01B human–machine interface (HMI) to form a closed-loop control structure. Experimental validation was performed under both spontaneous and constant load conditions. The PIDAT method consistently demonstrated superior performance compared to classical Ziegler–Nichols tuning, achieving steady-state errors in no-load tests below 1.70 % and under 0.8% in loaded conditions. Furthermore, the system achieved settling times below 9 s and recovered from load disturbances in less than 4 s. These results validate the proposed PIDAT system as an accurate, fast, and adaptive control solution, reducing the need for manual tuning and enhancing robustness in dynamic industrial environments.